2003
DOI: 10.1002/bit.10803
|View full text |Cite
|
Sign up to set email alerts
|

Optknock: A bilevel programming framework for identifying gene knockout strategies for microbial strain optimization

Abstract: The advent of genome-scale models of metabolism has laid the foundation for the development of computational procedures for suggesting genetic manipulations that lead to overproduction. In this work, the computational OptKnock framework is introduced for suggesting gene deletion strategies leading to the overproduction of chemicals or biochemicals in E. coli. This is accomplished by ensuring that a drain towards growth resources (i.e., carbon, redox potential, and energy) must be accompanied, due to stoichiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
986
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,137 publications
(995 citation statements)
references
References 42 publications
5
986
1
3
Order By: Relevance
“…The slightly higher acetate accumulation in the batch phase observed for E. coli MDS40 may indicate that overflow metabolism can occur more easily in the deletion strain; however, more precise metabolic studies are necessary to clarify this point. Mathematical models of E. coli have demonstrated higher yields of certain metabolites as a result of gene deletions (Burgard et al, 2003); however, these models did not account for the specific genes deleted to create E. coli MDS40, due to lack of information regarding these genes. In all, the multiple deletion strain performs comparably to its parent strain under industrial conditions.…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…The slightly higher acetate accumulation in the batch phase observed for E. coli MDS40 may indicate that overflow metabolism can occur more easily in the deletion strain; however, more precise metabolic studies are necessary to clarify this point. Mathematical models of E. coli have demonstrated higher yields of certain metabolites as a result of gene deletions (Burgard et al, 2003); however, these models did not account for the specific genes deleted to create E. coli MDS40, due to lack of information regarding these genes. In all, the multiple deletion strain performs comparably to its parent strain under industrial conditions.…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…Applications of the E. coli GEM range from pragmatic to theoretical studies, and can be classified into five general categories ( Fig. 3): 1) metabolic engineering [20][21][22][23][24][25][26][27][28][29][30] ; 2) biological discovery [31][32][33][34][35][36][37] ; 3) assessment of phenotypic behavior 19, ; 4) biological network analysis [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] ; and 5) studies of bacterial evolution [80][81][82] . The in silico methods used to probe the E. coli GEM in each study are summarized in Fig.…”
Section: Ask Not What You Can Do For a Reconstruction But What A Recmentioning
confidence: 99%
“…Through the application of computational methods that incorporate linear, mixed integer linear, and non-linear programming, it has been demonstrated that model-directed strain design can lead to increased metabolite production [20][21][22][23][24][25][26][27][28][29][30] . In these studies, the E. coli GEM is principally used to analyze the metabolite production potential of E. coli and identify metabolic interventions needed to enable the production of the product of interest.…”
Section: Applications Of Gems To Metabolic Engineering Of E Colimentioning
confidence: 99%
See 2 more Smart Citations